Evaluation of glycemic response and starch digestibility in Korean rice toward the development of low GI rice - Lee, Chang-Min; Jeong, O-Young; Park, Hyun-Su; Seo, Jeonghwan; Park, Songhee; Lee, Keon-Mi; Jin, Mina; Choi, Il-Ryong; Han, Jae-Hyuk (Frontiers in Plant Science, 2025)
The global rise in type 2 diabetes has intensified the need for dietary strategies that promote glycemic control, including the development of functional staple foods with a low glycemic index (GI). In this study, we assessed 16 Korean rice accessions for grain morphology, biochemical composition, starch digestibility, and glycemic response to identify promising candidates for low GI rice breeding. Substantial variation was observed in amylose (4.3–41.8%) and protein content (6.09–9.28%), both key factors influencing starch hydrolysis and postprandial glucose levels. In vitro GI assays showed that seven accessions had GI values below 60, including Dodamssal, Goami2, and Goami4, which were characterized by high resistant starch (RS) content. Interestingly, Seullomi1 and Seullomi2 maintained low-to-intermediate GI values, associated with elevated proportions of slowly digestible starch (SDS), moderate-to-high amylose content resistance to enzymatic digestion. Starch digestibility profiling confirmed that these lines retained higher SDS content even after cooking, suggesting greater resistance to enzymatic hydrolysis. In vivo murine study (n = 5 per group) further validated these findings, with Seullomi1, Seullomi2, and Dodamssal showing significantly reduced blood glucose spikes at 30 minutes compared with Sindongjin, a commercial Korean rice variety. Complementary textural analysis revealed that the Seullomi lines preserved moderate hardness and stickiness, traits favorable for consumer acceptance. Collectively, these results establish Seullomi1 and Seullomi2 as promising prototypes for the development of functional rice varieties that provide glycemic control with acceptable textural quality, thereby facilitating the breeding of rice to mitigate the risk of type 2 diabetes.